OPTIMALISASI APBD DALAM PERSPEKTIF PERFORMANCE BUDGET - Syafputro, Eko; Ibrahim, Mariaty (Jurnal Kebijakan Publik, 2013)
This study aimed to knowingthe efficiency of performance budget on APBD Rokan Hulu calculations period 2006-2010. ThirdKnowing performance rationality budget on APBD Rokan Hulu calculations period 2006-2010.This research is descriptive quantitative and qualitative or conclusive, quantitative data obtainedthrough analysis of the theory of rationality associated with performance budgeting APBD RokanHulu. The research proves that analysis of qualitative effectiveness of performance budgetingAPBD Rokan Hulu calculations period 2006-2010 are in the good category.